EFICIENCY OF KNOWLEDGE USE FOR ESTABLISHING - Rusu, Bianca; Hurloiu, Lacramioara; Hurloiu, Iulian; Zarnescu, Odi Mihaela (Annals of Spiru Haret University. Economic Series, 2020)
The research and development field provides driving forces of economic growth. EU economy, including the national economies under the impact of scientific research and inventions results, turn into a multi-structural system. The intellectual development of the society is the most powerful productive force